FRI0052 INFLUENCE OF RHEUMATOID ARTHRITIS ON THE CLINICAL AND BIOLOGICAL PROFILE OF TYPE-2 DIABETES MELLITUS. (13th June 2020) - Avouac, J.; Elhai, M.; Forien, M.; Sellam, J.; Eymard, F.; Moltó, A.; Gossec, L.; Banal, F.; Daminano, J.; Dieudé, P.; Allanore, Y.
Abstract : Background: Type-2 diabetes and rheumatoid arthritis (RA) are two chronic diseases characterized by tissue inflammation and insulin resistance. To date, no data have evaluated the influence of RA-induced joint and systemic inflammation on the course of type-2 diabetes. Objectives: To study the impact of RA on type-2 diabetes Methods: Observational, multicenter, cross-sectional usual-care study, including 7 rheumatology centers. This study included over a 24-month period consecutive patients with type-2 diabetes and RA, fulfilling the 2010 ACR / EULAR criteria, and diabetic controls with osteoarthritis (OA). The following data were collected: demographics, disease activity and severity indices, current treatment for RA and diabetes, history and complications of diabetes. A systematic blood test was performed, assessing inflammatory (CRP levels) and metabolic (fasting glycemia and insulin levels, HbA1c) parameters. The HOMA2%B (insulin secretion) and HOMA2%S (tissue insulin sensitivity) indices (HOMA calculator, © Diabetes Trials Unit, University of Oxford) were used to assess insulin resistance. Ra and OA patients were compared using parametric tests after adjusting for age and BMI. A multivariate logistic regression was performed ti identify factors independently associated with insulin resistance. Results: We included 122 RA patients (74% women, mean age 64+/-11 years, mean disease duration 15+/-11 11 years, 75% with positive ACPA antibodies and 64% with erosive disease) and 54 controls with OA. 64% of RA patients were treated with oral corticosteroids <10 mg/day, 65% received methotrexate and 53% received targeted biological therapies. The characteristics of type-2 diabetes in the 54 OA patients corresponded to severe insulin-resistant diabetes: age> 65 years, high BMI> 30 kg/m 2, mean HbA1c 7.3%+/-11 1.3%, 30% of insulin requirement, high frequency of other cardiovascular risk factors, macroangiopathy found in almost half of patients and biological criteria of insulin resistance (elevation of HOMA2%B and decrease of HOMA2%S). RA patients with type-2 diabetes had a younger age (64+/-11 years vs. 68+/-12 years, p=0.031) and lower BMI (27.7+/-11 5.5 vs. 31.5+/-11 6.3, p<0.001). These patients also had severe diabetes (HbA1c 7.0%+/-11 1.2%, 29% of insulin requirement, 43% of macroangiopathy) with an insulin resistance profile identical to OA controls. After adjusting for age and BMI, RA patients had a significantly increased insulin secretion compared to OA patients (HOMA2%B: 83.1+/-11 65.2 vs. 49.3+/-11 25.7, p=0.023) as well as a significant reduction of insulin sensitivity (HOMA2%S: 61.1+/-11 31.6 vs. 92.9+/-11 68.1, p=0.016). This insulin resistance was associated with the inflammatory activity of RA, with a negative correlation between the HOMA2%S and the DAS28 (r=-0.28, p=0.027). The multivariate logistic regression confirmed the independent association between the HOMA2%S index and DAS28 (OR: 3.93, 95% CI 1.02-15.06), as well as high blood pressure (OR: 1.29, 95% CI 0.33-1.99 CI). Conclusion: RA patients with type-2 diabetes displayed severe, poorly controlled diabetes, highlighting the burden of comorbidities associated with RA. The clinical-biological profile of diabetic RA patients was severe insulin-resistant diabetes, with a biological profile of insulin resistance linked to the inflammatory activity of the disease. These findings may have therapeutic implications, with the potential targeting of insulin resistance through the treatment of joint and systemic inflammation. Acknowledgments: Société Française de Rhumatologie (research grant) Bristol Myers Squibb (research grant) Disclosure of Interests: Jérôme Avouac Grant/research support from: Pfizer, Bristol Myers Squibb, Consultant of: Sanofi, Bristol Myers Squibb, Abbvie, Boerhinger, Nordic Pharma, Speakers bureau: Sanofi, Bristol Myers Squibb Abbvie, MSD, Pfizer, Nordic Pharma, Muriel ELHAI: None declared, Marine Forien: None declared, Jérémie SELLAM: None declared, Florent Eymard Consultant of: Regenlab, Anna Moltó Grant/research support from: Pfizer, UCB, Consultant of: Abbvie, BMS, MSD, Novartis, Pfizer, UCB, Laure Gossec Grant/research support from: Lilly, Mylan, Pfizer, Sandoz, Consultant of: AbbVie, Amgen, Biogen, Celgene, Janssen, Lilly, Novartis, Pfizer, Sandoz, Sanofi-Aventis, UCB, Frédéric Banal: None declared, Joel Daminano: None declared, Philippe Dieudé: None declared, Yannick Allanore Shareholder of: Sanofi, Roche, Consultant of: Actelion, Bayer, BMS, Boehringer Ingelheim, Inventiva, Sanofi